РЕЗУЛЬТАТЫ ИСПЫТАНИЯ ТЕХНОЛОГИИ ПЕРЕРАБОТКИ РАДИОЭЛЕКТРОННОГО ЛОМА - Теляков А.Н.; Иконин Л.В. (My University, 2006)
Представлены результаты промышленной переработки отходов, содержащих драгоценные металлы, на стадиях разборки, сортировки и обогащения радиоэлектронного лома, плавки и электролиза, проведенные в промышленных условиях действующего предприятия.

In given work material are presented results of earning one's living conversion of departures, containing noble metals, on stages of stripping, sorting and enriching radioelectronic crowbar, swimming trunks and electrolysis, conducted in earned one's living conditions of acting enterprise.
Keywords: 253.07